2017
DOI: 10.1002/acm2.12202
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the medical physics education and training landscape

Abstract: PurposeThe education and training landscape has been profoundly reshaped by the ABR 2012/2014 initiative and the MedPhys Match. This work quantifies these changes and summarizes available reports, surveys, and statistics on education and training.MethodsWe evaluate data from CAMPEP‐accredited program websites, annual CAMPEP graduate and residency program reports, and surveys on the MedPhys Match and Professional Doctorate degree (DMP).ResultsFrom 2009–2015, the number of graduates from CAMPEP‐accredited gradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…With the widespread implementation of specialized techniques such as intensity modulated radiation therapy (IMRT), stereotactic radiation therapy (SRS/SBRT), the demand for qualified medical physicists has grown profoundly. To match this need, the education and training for medical physicist pre‐ and post‐graduation has seen an unprecedented change in past few years . Along with the clinical training, the research component of medical physics has also been encouraged; hence advanced.…”
Section: Opening Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…With the widespread implementation of specialized techniques such as intensity modulated radiation therapy (IMRT), stereotactic radiation therapy (SRS/SBRT), the demand for qualified medical physicists has grown profoundly. To match this need, the education and training for medical physicist pre‐ and post‐graduation has seen an unprecedented change in past few years . Along with the clinical training, the research component of medical physics has also been encouraged; hence advanced.…”
Section: Opening Statementmentioning
confidence: 99%
“…The pursuit of certification has reshaped the educational pathway to become a practicing medical physicist. When the ABR introduced the 2012/2014 initiative, the path became very standardized; equivalent of a physics minor as an undergraduate, a fixed core curriculum as a graduate student and final clinical training as a resident, both from CAMPEP accredited institutions . To become accredited, CAMPEP requires that institutions have qualified faculty that teach a specific core curriculum to prepare students to enter the field of medical…”
Section: Opening Statementmentioning
confidence: 99%
“…Alternatively, we could allow the free market to correct for the potential surplus in these programs by requiring them to post their residency placement statistics. Loughery et al . have reported that between 2011 and 2015, placement rates for only ten programs were > 50%; four programs had 0%, and 11 others had < 20%.…”
Section: Against the Proposition: Joann I Prisciandaro Phdmentioning
confidence: 99%
“…While the current supply of radiation oncologists and radiation oncology physicists is sufficient to meet clinical demand ( 7, 8 ), there is a strong need to further invest in our research infrastructure if we are to contribute significantly to future improvements in cancer care. As suggested in a recently published editorial, ‘‘‘.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, more trainees with a Ph.D. in addition to their medical degree are matching into radiation oncology residency positions than into any other medical specialty ( 9 ). In addition, we are currently producing significantly more medical physics graduates than we can expect to be absorbed into clinical practice ( 8 ). In stark contrast, radiobiologists are becoming scarce, both in the clinical setting and in research institutions ( 2, 10, 11 ).…”
Section: Introductionmentioning
confidence: 99%